Protocol for the RETHINK study: a randomised, double-blind, parallel-group, non-inferiority clinical trial comparing acetaminophen and NSAIDs for treatment of chronic pain in elderly patients with osteoarthritis of the hip and knee - Tempei Miyaji; Mototsugu Shimokawa; Hiroyuki Aono; Sadamoto Zenda; Makoto Endo; Yasuharu Nakashima; TOSHIHIKO HARA; Shinya Kawahara; Taishi Sato; Masami Tokunaga; Taro Mawatari; Tsutomu Kawano; et al. (BMJ Open, 2023)
Introduction In patients with chronic pain, oral analgesics are essential treatment options to manage pain appropriately, improve activities of daily living abilities and achieve a higher quality of life (QOL). It is desirable to select analgesics for elderly patients based on comparative data on analgesic effect and risk of adverse events; however, there are few comparative studies so far. The purpose of this study is to determine whether the efficacy and safety of acetaminophen are non-inferior to non-steroidal anti-inflammatory drugs (NSAIDs) in the treatment of chronic pain associated with osteoarthritis of the hip and knee in elderly patients.Methods and analysis This study is a multicentre, randomised controlled, double-blind, parallel-group study to compare the analgesic effect and adverse events between acetaminophen or NSAIDs (loxoprofen or celecoxib). A total of 400 elderly patients with osteoarthritis of the hip and knee will be recruited from five institutions in Japan. Patients of 65 years or older with osteoarthritis-related pain will be registered and randomly assigned to acetaminophen, loxoprofen or celecoxib with 2:1:1 allocation. The primary endpoint is change in the Brief Pain Inventory (BPI) item 3 (worst pain) score from baseline to week 8. The secondary endpoints are BPI item 3 score change from baseline to week 4, health-related QOL measured by Short Form-8 Health Survey, and occurrence of adverse events including gastrointestinal disorders and abnormal liver function. Data will be analysed in accordance with a predefined statistical analysis plan.Ethics and dissemination This study protocol was approved by the Kyushu University Hospital Certified Institutional Review Board for Clinical Trials on 28 January 2021 (KD2020004) and the chief executive of each participating hospital. The results of the study will be submitted to international peer-reviewed journals, and the main findings will be presented at international scientific conferences.Trial registration number jRCTs071200112.